Speech tempo consonant deletion - Victor Edosa Omozuwa (Studies in African Linguistics, 1989)
Speech tempo, vowel contraction/elision, and consonant deletion are common phonetic features of the Edo language spoken in Oredo, Orhionmwo, and Ovia Local Government Areas of Bendel State, Nigeria. Vowel contraction/elision in rapid speech usually occurs in word boundaries in larger constructions and often results in tonal modifications of such utterances. This paper focuses on speech tempo as it affects consonant deletion in Edo nouns. Two speech tempos, slow and rapid, will be used in explaining the presence or absence of consonant deletion in the language. Consonant deletion in rapid speech occurs exclusively in nouns. The tonal melody, the number of syllables, and the meanings of such nouns are not affected by consonant deletion. Consonant deletion in Edo nouns follows a regular pattern depending on the articulatory properties of the consonants in a given sequence.